A mass-balance approach to evaluate arsenic intake and excretion in different populations. (August 2022) - Beene, Daniel; Collender, Philip; Cardenas, Andres; Harvey, Charles; Huhmann, Linden; Lin, Yan; Lewis, Johnnye; LoIacono, Nancy; Navas-Acien, Ana; Nigra, Anne; Steinmaus, Craig; van Geen, Alexander
Highlights: Arsenic intake and excretion are compared in a consistent manner across rural Bangladesh, Navajo Nation, and Northern Chile. Considering a primary water source only for As intake is inconsistent with mass-balance in all 3 populations. Additional sources of As in water, food, and house dust bring intake closer to As excretion in 2 out of 3 populations. Deviations from mass-balance between intake and excretion of certain toxicants helps detect exposure misclassification. Abstract: Unless a toxicant builds up in a deep compartment, intake by the human body must on average balance the amount that is lost. We apply this idea to assess arsenic (As) exposure misclassification in three previously studied populations in rural Bangladesh (n = 11, 224), Navajo Nation in the Southwestern United States (n = 619), and northern Chile (n = 630), under varying assumptions about As sources. Relationships between As intake and excretion were simulated by taking into account additional sources, as well as variability in urine dilution inferred from urinary creatinine. The simulations bring As intake closer to As excretion but also indicate that some exposure misclassification remains. In rural Bangladesh, accounting for intake from more than one well and rice improved the alignment of intake and excretion, especially at low exposure. In Navajo Nation, comparing intake and excretion revealed home dust as an important source. Finally, in northern Chile, while food-frequency questionnaires and urinary As speciation indicate fish and shellfish sources, persistent imbalance of intake and excretion suggests imprecise measures of drinking water arsenic as a major cause of exposure misclassification. The mass-balance approach could prove to be useful for evaluating sources of exposure to toxicants in other settings.